Serpentine Overburden Products—Nature-Inspired Materials for Metal Detoxification in Industrially Polluted Soil - Marina V. Slukovskaya; Anna G. Petrova; Liubov A. Ivanova; Tatiana K. Ivanova; Irina A. Mosendz; Andrey I. Novikov; Anna A. Shirokaya; Mariia V. Kovorotniaia; Taras L. Panikorovskii; Irina P. Kremenetskaya (Toxics, 2023)
The possibility of plants growing on serpentine soils and the ability of serpentine minerals to accumulate significant amounts of metals was the basis for developing a method for using serpentine-containing materials to restore vegetation in areas with a high level of metal pollution. Serpentine-containing products obtained from phlogopite mining overburden (Kovdor, Murmansk region, Russia) with and without thermal activation were used in a field experiment on the remediation of industrially polluted peat soil. According to the geochemical mobility of the components, one of four fractions was allocated depending on the acidic (HCl) concentration of the solution used for the material treatment: readily mobile (0.001 mol/L), mobile (0.01 mol/L), potentially mobile (0.1 mol/L), and acid-soluble (1.0 mol/L). This study showed that the addition of serpentinites to peat soil changed the fraction composition. The most significant changes were noted for serpentinite components such as Ca and Mg: their concentrations increased 2–3 times even in the smallest portion of serpentine material. On the contrary, the contents of metals in the readily mobile fraction decreased 3–18, 3–23, 5–26, and 2–42 times for Cu, Ni, Fe, and Al, respectively. The main factor causing the decrease in metal mobility was the pH rise due to the release of Ca and Mg compounds into the soil solution. This study showed that the addition of serpentine-containing material at 25 vol.% to peat soil was sufficient to create a geochemical barrier with a stable-functioning vegetation cover. All serpentine-containing materials are recommended for the remediation of large industrially polluted areas.